Retinal Optical Coherence Tomography Angiography Parameters Between Patients With Different Causes Of Chronic Kidney Disease - Meng Hsien Yong; Ming Yean Ong; Kuan Sze Tan; Siti Husna Hussein; Ayesha Mohd Zain; Rozita Mohd; Ruslinda Mustafar; Wan Haslina Wan Abdul Halim (Frontier, 2024)
Frontiers in Cellular Neuroscience Volume 16 Page (1-8)